Spatial and seasonal patterns in fish assemblage in Córrego Rico, upper Paraná River basin - Takahashi,Erico L. H (2013)
The upper Paraná River basin drains areas of intensive industry and agriculture, suffering negative impacts. The Córrego Rico flows through sugar cane fields and receives urban wastewater. The aim of this work is to describe and to compare the fish assemblage structure in Córrego Rico. Six standardized bimonthly samples were collected between August 2008 and June 2009 in seven different stretches of Córrego Rico. Fishes were collected with an experimental seine and sieves, euthanized, fixed in formalin and preserved in ethanol for counting and identification. Data were recorded for water parameters, instream habitat and riparian features within each stretch. Non-metric multidimensional scaling, species richness and diversity analysis were performed to examine spatial and seasonal variation in assemblage structure. Fish assemblage structure was correlated with instream habitat and water parameters. The fish assemblage was divided in three groups: upper, middle and lower reaches. High values of richness and diversity were observed in the upper and lower stretches due to connectivity with a small lake and Mogi Guaçu River, respectively. Middle stretches showed low values of richness and diversity suggesting that a small dam in the middle stretch negatively impacts the fish assemblage. Seasonal differences in fish assemblage structure were observed only in the lower stretches.